Особливості реалізації конструктивізму в системі підготовки вчителів та підходах до викладання іноземної мови у США - Леврінц Маріанна; Lőrincz Marianna; Levrints Marianna (Видавництво СумДПУ імені А. С. Макаренка, 2019)
Резюме. У статті розглядаються особливості реалізації засад конструктивізму в системі підготовки вчителів іноземних мов, а також підходів до викладання іноземних мов, зумовлених впливом конструктивізму як концептуальної основи освіти в США. Застосовано низку комплементарних методів дослідження, а саме аналіз, синтез теоретико-практичного доробку, узагальнення прогресивного педагогічного досвіду. Виявлено, що парадигмальні зміни у сферах викладання іноземної мови та підготовки фахівців відповідної кваліфікації, спричинені впливом конструктивізму, зумовили переосмислення змісту, організації та практичних підходів у системі підготовки вчителів іноземної мови у США. У галузі викладання іноземної мови під впливом конструктивізму оформлюється низка сучасних навчальних підходів, як наприклад, навчання мови через виконання завдань, навчання іноземної мови через зміст навчальних дисциплін тощо.

Abstract. Constructivism has emerged as a central conceptual orientation of the American educational system, thus exerting a considerable impact on the theoretical discourse, approaches to foreign language teaching and respectively on the foreign language teacher education. This paper thus reflects on the nature of this influence in terms of implementation of underlying principles of constructivism into the system of language teacher education, its potential benefits, as well as approaches to foreign language instruction in the USA. A number of complementary research methods have been applied, namely analysis, synthesis, generalization of effective pedagogical practices. The new philosophical-epistemological stance has underscored the necessity for re-conceptualizing and reorganizing traditional models of foreign language teacher preparation, together with reformulation of roles assumed by language teachers in various socio-cultural contexts. Constructivist paradigm has brought about a dramatic shift in the field of foreign language teaching, leading to the development of a number of innovative approaches, for instance, task-based language learning, content-oriented language learning, cognitive academic language learning approach, blended learning and some others. Many of the contemporary approaches require on the teacher’s part integrated knowledge of linguistics and subject-specific content, target language command, together with the knowledge of disciplines included in the curriculum of education institutions, for instance, history, mathematics etc. Language teacher educators are thus posed with serious challenges, who are expected to bring into congruence theoretical advancements prompted by constructivism research with multifarious aspects of teacher education practice, involving modification of didactic approaches, principles, techniques, content of teacher education, its various tiers, e.g. teacher induction, development etc. Benefits of incorporating the underlying principles of constructivism into language teacher education are substantial as compared to more traditional models, in terms of development of professional awareness, overcoming stereotypical views and biases of future teachers. Nevertheless, constructivism should be viewed as only one of the possible alternatives in the conceptual foundation of language teacher education. Limiting the approaches and content of teacher education to one conceptual framework may result in uncritical, skewed attitude of future teachers towards their understanding of the nature of teaching and professional development.

Резюме. В статье рассматриваются особенности реализации принципов конструктивизма в системе подготовки учителей иностранных языков, а также подходов к преподаванию иностранных языков, обусловленных влиянием конструктивизма как концептуальной основы образования в США. Применен ряд комплементарных методов исследования, а именно: анализ, синтез, обобщение прогрессивного педагогического опыта. Выявлено, что парадигмальные изменения в сферах преподавания ИЯ и подготовки специалистов соответствующей квалификации, вызванные влиянием конструктивизма, обусловили переосмысление содержания, организации и практических подходов в системе подготовки учителей ИЯ в США. В области преподавания ИЯ под влиянием конструктивизмa оформляется ряд современных учебных подходов, например, обучение языку посредством выполнения учебных задач, обучение ИЯ через содержание учебных дисциплин и т.д.
Implementing constructivism in the system of teacher education and approaches to foreign language teaching in the USA
Особенности реализации конструктивизма в системе подготовки учителей и подходах к преподаванию иностранных языков в США
https://pedscience.sspu.edu.ua/wp-content/uploads/2019/07/319.pdf
Keywords: конструктивізм; майбутній учитель; підходи до викладання іноземної мови; навчальні технології